2016
DOI: 10.1037/sah0000014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of self-stigma, quality of life, somatic complaints, and depression among people with schizophrenia: A pilot study applying kernel smoothers.

Abstract: The aims of this study are to verify this sequential structure and to determine if self-stigma is associated with lower quality of life (QoL) and depression. A total of 160 patients with schizophrenia participated in this study. Each completed the Self-Stigma Scale-Short Form (SSS-S), the World Health Organization (WHO) questionnaire on the Quality of Life, Brief Form (WHOQOL-BREF), and the Depression and Somatic Symptoms Scale (DSSS) instruments. Dynamic changes of the measures of self-stigma and related QoL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 64 publications
5
30
0
Order By: Relevance
“…Thus, healthcare providers can use the Affiliate Stigma Scale to compare the affiliate stigma between caregivers of people with dementia and other mental disorders after its psychometric properties are established for caregivers of people with dementia. Third, the Affiliate Stigma Scale was designed on the basis of cognitive behavioral theory, and the mechanism of self-stigma was examined using empirical data [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, healthcare providers can use the Affiliate Stigma Scale to compare the affiliate stigma between caregivers of people with dementia and other mental disorders after its psychometric properties are established for caregivers of people with dementia. Third, the Affiliate Stigma Scale was designed on the basis of cognitive behavioral theory, and the mechanism of self-stigma was examined using empirical data [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Internalized stigma is suggested to consist of three components, including stereotypes, prejudice, and discrimination, that correspond to cognition, affect, and behavior, respectively (Lin et al, 2016). Therefore, the origin of the internalized stigma begins from the unfriendly environment, for example, the beliefs of public that people with mental illness are dangerous (Corrigan and Roe, 2012).…”
mentioning
confidence: 98%
“…Consequently, people with mental illness may have unequal access to resources, such as education, living in a community, and quality healthcare (Centers for Disease Control and Prevention, 2012). Moreover, they may also feel self-stigma (i.e., stigma directed at themselves or internalized stigma) that causes them profound psychological adversity, demoralization, feelings of hopelessness, lowered self-esteem and self-efficacy, poor quality of life, reduced adherence to psychiatric medication regimes, and others (Boyd et al, 2014;Corrigan et al, 2009;Huang and Lin, 2015;Lin et al, 2016).…”
mentioning
confidence: 98%
“…Self-stigma is one of the most important factors in an individual's SQoL (Lin, Chang, Wu, & Wang, 2016). Although several theories have been proposed to conceptualise self-stigma (Chang, Lin, Gronholm, & Wu, 2016;Corrigan, Watson, & Barr, 2006;Livingston & Boyd, 2010), there is a consensus of opinion that people with self-stigma have internalised a perceived stigma.…”
mentioning
confidence: 99%
“…In a patient with mental illness, self-stigma tends to reduce his/her motivation to accept treatment (Fung, Tsang, & Corrigan, 2008;Tsang, Fung, & Chung, 2010). Studies have demonstrated a causal relationship between an individual's self-stigma and SQoL (Chan & Mak, 2014;Mashiach-Eizenberg, HassonOhayon, Yanos, Lysaker, & Roe, 2013;Lin et al, 2016); others have shown that self-stigma negatively affects the self-esteem of a person with a mental illness (Corrigan & Watson, 2002;Corrigan et al, 2006;Lysaker, Roe, Ringer, Gilmore, & Yanos, 2012). As self-esteem has been found to mediate between self-stigma and many health-related outcomes such as depression and impaired social functioning (Yanos, Roe, & Lysaker, 2010;Yanos, Roe, Markus, & Lysaker, 2008), it is not surprising that researchers have proposed an evidence-based model of self-esteem as a mediating factor between self-stigma and an individual's SQoL (Mashiach-Eizenberg et al, 2013).…”
mentioning
confidence: 99%